How Radical Was the Enlightenment? What Do We Mean by Radical? (Diametros, 2014)
The Radical Enlightenment has been much discussed and its original meaning somewhat distorted. In 1981 my concept of the storm that unleashed a new, transnational intellectual movement possessed a strong contextual and political element that I believed, and still believe, to be critically important. Idealist accounts of enlightened ideas that divorce them from politics leave out the lived quality of the new radicalism born in reaction to monarchical and clerical absolutism. Taking the religious impulse seriously and working to defang it of bellicosity would require years of labor. First all the world’s religions had to be surveyed, see Picart’s seven folio volumes; and Rousseau’s Savoyard vicar had to both preach and live religion simply as true virtue; and finally Jefferson editing the Bible so as to get the irrational parts simply removed, thus making people more fit to grant a complete religious toleration. Throughout the century all these approaches to revealed religion may be legitimately described as radical. Each produced a different recommendation for its replacement. As I have now come to see, the pantheism I identified in 1981 would lead in many directions, among them lay the search to understand all human religiosity and to articulate a universal natural religion.
Keywords: Atheism; materialism; absolutism; French Protestant refugees; Dutch cities; religious toleration; Bernard Picart; Jonathan Israel; English freethinkers; Papal condemnation; Rousseau; pantheism; Jefferson